A STUDY OF SOME PARAMETERS OF THE EXTERNAL RESPIRATORY FUNCTION AND THEIR RELATIONSHIP TO THE CLINICAL ACTIVITY IN PATIENTS WITH RHEUMATOID ARTHRITIS - D. V. Bestaev; A. V. Volkov; D. E. Karateev; E. L. Nasonov (Научно-практическая ревматология, 2014)
Pulmonary pathology is diagnosed in patients with rheumatoid arthritis (RA). The external respiratory function (ERF) examination is widely used to assess the functional capacity of the lungs. Objective. To evaluate ERF in patients with RA. Material and methods. The study included 155 patients with RA. A MasterScreen Body plethysmograph (Erich Jaeger) was used to determine the ERF parameters (diffusing lung capacity, DLC; forced inspiratory vital capacity, FIVC; forced expiratory volume in 1 second, FEV1; total lung capacity, TLC; the FEV1/FIVC ratio, and the modified Tiffeneau index). DLC was measured by the single-breath method. ERF parameters were represented as a percentage of the appropriate value for a given gender, age, and height of the patient. Results. Of the 155 examined patients with RA, a decrease in the DLC parameter was detected in 107 (69%), while in 87 (81%) patients, the decrease was less than 10% of the proper values. An analysis of the state of the ERF parameters revealed a decrease in FEV1 in 48 (31%) patients, FIVC in 41 (27%) patients, and TLC in 36 (23%) patients. The restrictive type of lung ventilation was determined in 27% of patients, bronchial obstruction in 31% of patients, an iso- lated decrease in DLC in 12% of patients with RA. In 31% of cases, no deviations of the ERF parameters from normal values were found. A statistically significant negative correlation between the clinical activity of RA and the DLC level (r = -0.59; p<0.05) was found. Conclusion. The study revealed a high frequency of variation in the ERF parameters in patients with RA. In most cases, the variation was demonstrated by DLC. The obstructive changes were prevalent among RA patients. The high percentage of smokers among RA patients with the obstructive type of ventilation may indicate the influence of smok- ing on the development of bronchial obstruction. Our work revealed the significant relationship between the degree of RA activity and the DLC value.